Morphometric study of encephalic lesions in aborted bovine fetuses naturally infected by two subpopulations of Neospora caninum - Dorsch, Matías; Moore, Prando Dadin; Regidor Cerrillo, Javier; Scioli, Maria Valeria; Morrell, Eleonora Lidia; Canton, German Jose; Ortega Mora, Luis; Hecker, Yanina (Springer, 2022)
Neospora caninum is a major reproductive disease in cattle worldwide. In the Argentinian Humid Pampa, the seroprevalence, incidence of abortions, and economic losses due to neosporosis are considerably higher in dairy than in beef cattle. Despite this, we recently demonstrated that N. caninum subpopulations are indistinctly distributed in both dairy and beef production systems. The association between genotypic characteristics defined by microsatellite analysis and the virulence of the different strains—particularly with regard to the severity and extension of histological lesions—is largely unknown. Herein, we used a morphometric approach to analyze encephalic lesions in 62 bovine fetuses spontaneously infected by N. caninum. Morphometric parameters (average size of focal lesions, number of foci/cm2 and the percentage of the section affected by lesions) were compared according to the N. caninum subpopulations found in our previous microsatellite genotyping analysis, animal biotype (beef versus dairy), and fetal age (second stage of gestation versus third stage). The average size of the lesions differed significantly among fetuses with different gestational ages; however, no significant differences among animal biotypes or genotypic patterns were found. Further research into the genetic, molecular, and husbandry factors that could account for this greater impact in Argentinian dairy herds is needed.